The role of stereotypes in cross-cultural communication - Shutova V. D. (Patriotism as a factor of social-economic development of Russia, 2019)
the article reveals main features of stereotypes in different cultures. Also, the article deals with the issue of cross-cultural communication using a foreign language.
Keywords: культура; коммуникация; стереотип; culture; communication; stereotype